The anthropology of human obsolescence. Hyper-consumption, technophilia and commercial speed - Polo Blanco, Jorge (Revista de Filosofía, 2018)
In this paper we wish to address a problem which has to do with the growing obsolescence of human beings in the context of societies which are at once ultra-technological, hyper-consumerist and based around a market economy. We aim to examine critically and in detail the psychosocial and anthropological conditions of a world where women and men are being overtaken by a sometimes explosive combination of commercial speed and globalised capitalism. Technophilia, the true fetishism of our age, operates at full capacity as one of the legitimising ideological discourses of that historical process by means of which men are dwarfed by their own creation; men overwhelmed by the crushing power of a set of technoscientific developments which - and this is crucial - unfold with relative and worrying autonomy and following dynamics which often do not respond to actual human needs. Technology, which is never politically innocent, acquires uncommon proportions and scope when, in addition, its deployment responds to a cumulative capitalist logic of a boundless nature. It is this issue, therefore, which we aim to elucidate from an anthropological and philosophical point of view.
Keywords: Human obsolescence; commercial speed; market societies; turbo-capitalism; technological fetishism.